Power, Violence and Revolution in Walter Benjamin and Hannah Arendt - Miralpeix, María Mercedes; Ortega Insaurralde, Carlos (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
In this paper we’ll analyze the concepts of power, violence and revolution in the reflections of Walter Benjamin and Hannah Arendt. These concepts are key for understanding the difficulties present in both authors when thinking on the problem of the emergence of new political agents in the publicpolitic space. In this context, what interests us is to explore a possible complementarity of the analyses of both Arendt and Benjamin with respect to this specific problematic, a complementarity that could, from our point of view, help to overcome those difficulties. In this sense, we will argue that, beyond the differences in the approaches of both authors with relation to the analysis of violence, power and revolution, they concur in the idea that, in a revolution, the creation of new political actors (Arendt) and the irruption of past political experiences (Benjamin) redefines the role of violence and power in the public-political space.
Keywords: Power; violence; revolution; Walter Benjamin; Hannah Arendt